Er:YAG LASER ASSISTED CAVITY PREPARATION AND RESTORATION PROTOCOL (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the optimal parameters of laser Er:YAG for treating dental caries in first permanent molars of children aged 9-12 years and assess pain and anxiety levels of the children.Subjects and methods: A cross-sectional study was conducted on 16 class I carious first permanent molars (ICDASTM levels 3, 4, 5) in 16 children. Pain levels were recorded using the Wong-Baker self-assessment scale and anxiety levels were measured by the Venham scale. Inclusion criteria included healthy pediatric patients, carious lesions without pulp exposure, and absence of periapical pathology and treatment was performed without administration local anesthesia.Results: The study demonstrated the effectiveness of laser Er:YAG in treating caries of the first permanent molars, with optimal settings: pulse energy of 400 mJ for enamel preparation, 300 mJ for dentin preparation and 150 mJ for created enamel surface roughness prior to adhesive restoration. Optimum operative at a frequency of 10 Hz, with moderate water and air flow. Pain levels were predominantly recorded no pain and anxiety levels were also predominantly comfortable and a strong correlation was observed between pain and anxiety levels.Conclusion: Based on the principle of minimally invasive and patient centered care, using Er:YAG laser can partially or completely replace traditional treatment with rotary instruments. In children, pain is a major factor leading to anxiety or lack of cooperation during caries treatment. Using Er:YAG laser has been proven to reduce pain, minimally invasive intervention, minimize noise and vibration due to the non-contact mode, therefore enhancing pediatric patient cooperation during dental procedures.
Keywords: Er:YAG laser, dental caries, pain, anxiety, optimal parameters.